Hodnocení finanční situace podniku a návrhy na její zlepšení - Podešva, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Cílem této diplomové práce je zhodnocení finanční situace podniku Zlínterm, s. r. o. v období let 2001 až 2005 prostřednictvím vybraných metod finanční analýzy. Práce obsahuje opatření a návrhy řešení stávající situace, které mohou vést ke zlepšení finanční situace podniku v jeho budoucím vývoji.

The goal of this master’s work is evaluation of the financial situation of the company Zlínterm, Ltd. within the years 2001 to 2005 at the basis of selected methods of the financial analysis. It contains proposals of possible solutions of identified problems which may lead to financial situation’s improvements of the company in its future development.
Evulation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: finanční analýza; účetní výkazy; elementární metody finanční analýzy; vyšší metody finanční analýzy; finanční poměrové ukazatele; financial analysis; financial statements; elementary methods of financial analysis; superior methods of financial analysis; financial ratios